2016
DOI: 10.1016/j.psychres.2016.06.039
|View full text |Cite
|
Sign up to set email alerts
|

Nonsuicidal self-injury and suicide attempts in Iraq/Afghanistan war veterans

Abstract: The present study examined the association between history of nonsuicidal self-injury (NSSI) and history of suicide attempts (SA) among 292 Iraq/Afghanistan veterans, half of whom carried a lifetime diagnosis of posttraumatic stress disorder (PTSD). Consistent with hypotheses, veterans who reported a history of NSSI were significantly more likely to report a history of SA than veterans without a history of NSSI. In addition, logistic regression demonstrated that NSSI remained a significant predictor of SA even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
43
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 39 publications
(70 reference statements)
4
43
2
Order By: Relevance
“…Cooper et al and Hawton et al concluded that, in the first 12 months after self-harm, the risk of suicide was 30 or 49 times greater than the average, respectively (27,28). In three different studies, Kimbrel et al suggested that NSSIB was a robust predictor of suicidal ideation and suicide attempts in veterans with PTSD (29)(30)(31). Kaya et al from Turkey declared that NSSIB was a risk factor for suicidal depression and attempts (6).…”
Section: Discussionmentioning
confidence: 99%
“…Cooper et al and Hawton et al concluded that, in the first 12 months after self-harm, the risk of suicide was 30 or 49 times greater than the average, respectively (27,28). In three different studies, Kimbrel et al suggested that NSSIB was a robust predictor of suicidal ideation and suicide attempts in veterans with PTSD (29)(30)(31). Kaya et al from Turkey declared that NSSIB was a risk factor for suicidal depression and attempts (6).…”
Section: Discussionmentioning
confidence: 99%
“…Nonsuicidal self-injury (NSSI) is defined as deliberately damaging one's body tissue without conscious suicidal intent (Chapman et al, 2006; Kimbrel et al, 2016; Kimbrel et al, 2015; Kimbrel et al, 2014). The most common methods of NSSI include self-burning, self-cutting, self-hitting, and severe scratching (Klonsky, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…It is estimated that 6% of the U.S. general population will engage in NSSI at some point in their lifetime (Briere and Gil, 1998; Klonsky, 2011). Although NSSI has historically been viewed as more common among females than males, population-based studies of NSSI have consistently failed to find evidence for sex differences in rates of NSSI among adults (Kimbrel et al, 2016). NSSI has been associated with significantly increased risk of suicidal behavior in military and veteran samples (Bryan et al, 2015; Kimbrel et al, 2016; Kimbrel et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations